2007
DOI: 10.1111/j.1745-6592.2006.00123.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of a Chromate‐Contaminated Soil Site by in situ Gaseous Reduction

Abstract: A proof‐of‐concept field test for the treatment of hexavalent chromium in the vadose zone using in situ gaseous reduction was successfully completed by the U.S. Department of Energy and U.S. Department of Defense in a joint demonstration conducted at White Sands Missile Range, New Mexico. The test involved injecting hydrogen sulfide, diluted in air, into contaminated vadose zone sediment to reduce Cr(VI) to Cr(III). The gaseous mixture was injected directly into the contaminated sediment through a central inje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…In addition, the field test demonstrated that vadose zone treatment of contamination could be safely conducted using diluted hydrogen sulphide gas mixtures Thornton et al (2007) Naphthalene at a creosotecontaminated…”
Section: Bioremediation Of Oil Contaminated Mediamentioning
confidence: 99%
“…In addition, the field test demonstrated that vadose zone treatment of contamination could be safely conducted using diluted hydrogen sulphide gas mixtures Thornton et al (2007) Naphthalene at a creosotecontaminated…”
Section: Bioremediation Of Oil Contaminated Mediamentioning
confidence: 99%
“…2003 a ). Most of these facilities have soil Cr(VI) concentrations that exceed the regulatory limit of 30–240 mg Cr(VI)/kg of soil, with regulatory limits being State dependent. , Since the soils are exposed to the environment, precipitation events have the propensity to drive Cr(VI) through the soil profile into groundwater. The Cr(VI) moiety is generally considered to have limited retardation within the soil profile, and the potential for Cr(VI) transport to groundwater has been taken very seriously.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of vacuum into microbial fuel cells caused only slight changes in the community structure, but the metabolic activity changed significantly. The attachment between extracellular polymeric substances and one of the electrodes was much stronger, resulting in the generation of power that was seven times higher as compared with the atmospheric environment (Xiao et al 2013). Unfortunately, there is only one such report.…”
Section: Microbial Fuel Cellsmentioning
confidence: 99%